Physical and morphological characterization of chitosan/montmorillonite films incorporated with ginger essential oil - Souza, Victor Gomes Lauriano (2019)
This work was supported by CNPq - Brazil (grant number 200790/2014-5) and the MEtRICs unit which is financed by national funds from FCT/MCTES (UID/EMS/04077/2019). This work was also supported by the Associate Laboratory for Green Chemistry-LAQV which is financed by national funds from FCT/MCTES (UID/QUI/50006/2019) and UCIBIO, which is funded by national funds from FCT/MCTES (UID/Multi/04378/2019). It is also acknowledged the funding of CENIMAT by FEDER through the program COMPETE 2020 and National Funds through FCT-Portuguese Foundation for Science and Technology, under the project UID/CTM/50025/2019.